Communication strategy used by Spanish speakers of English in formal and informal speech. (June 2018) - Kouwenhoven, Huib; Ernestus, Mirjam; van Mulken, Margot
Research questions: Are emergent bilinguals sensitive to register variation in their use of communication strategies? What strategies do LX speakers, in casu Spanish speakers of English, use as a function of situational context? What role do individual differences play? Methodology: This within-speaker study compares Spanish second-language English speakers' communication strategy use in an informal, peer-to-peer conversation and a formal interview. Data and analysis: The 15 hours of informal and 9.5 hours of formal speech from the Nijmegen Corpus of Spanish English were coded for 19 different communication strategies. Findings/conclusions: Overall, speakers prefer self-reliant strategies, which allow them to continue communication without their interlocutor's help. Of the self-reliant strategies, least effort strategies such as code-switching are used more often in informal speech, whereas relatively more effortful strategies (e.g. reformulations) are used more in informal speech, when the need to be unambiguously understood is felt as more important. Individual differences played a role: some speakers were more affected by a change in formality than others. Originality: Sensitivity to register variation has not yet been studied within communicative strategy use. Implications: General principles of communication govern speakers' strategy selection, notably the protection of positive face and the least effort and cooperative principles.